2020
DOI: 10.1007/s10680-020-09570-0
|View full text |Cite|
|
Sign up to set email alerts
|

Beyond the Economic Gaze: Childbearing During and After Recessions in the Nordic Countries

Abstract: During the 2010s, fertility rates fell across the Nordic region. The onset of these declines seems linked to the Great Recession of 2008–2009, but their continuation cannot easily be linked to subsequent economic change. The 1990s, too, brought episodes of economic crises to the Nordic region that were followed by different degrees of fertility decline. In this study, we provide an empirical overview of parity-, age- and education-specific fertility developments in the five Nordic countries in the wake of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 65 publications
1
47
0
1
Order By: Relevance
“…Despite issues related to the health system's geographical and social equity (Ringard et al, 2013), the Norwegian welfare state is generally characterised by universal and equal access to services (Greve et al, 2021). These services include family policies, which scholars argue have kept the declining fertility rates at relatively high levels when the same rates have been declining more rapidly in other Western countries (Comolli et al, 2020). An analysis of Norwegian family policies concluded that there is a political consensus about children being a public good and a public responsibility, and that pronatalistic policies are legitimatised through reference to the people's welfare (Ellingsaeter, 2012).…”
Section: The Norwegian Contextmentioning
confidence: 99%
“…Despite issues related to the health system's geographical and social equity (Ringard et al, 2013), the Norwegian welfare state is generally characterised by universal and equal access to services (Greve et al, 2021). These services include family policies, which scholars argue have kept the declining fertility rates at relatively high levels when the same rates have been declining more rapidly in other Western countries (Comolli et al, 2020). An analysis of Norwegian family policies concluded that there is a political consensus about children being a public good and a public responsibility, and that pronatalistic policies are legitimatised through reference to the people's welfare (Ellingsaeter, 2012).…”
Section: The Norwegian Contextmentioning
confidence: 99%
“…Furthermore, the study period coincided with an economic crisis which may have accelerated the deinstitutionalisation process, although with little effect on other service provision. 34 Moreover, it may have influenced the composition of fathers (via health and socioeconomic selection into parenthood 35 ) as well as created lagged psychiatric health effects, indicated by increased suicide risks. 36 Although we attempted to account for selection bias by adjusting for pre-birth psychiatric hospitalisations and annual labour income, finding little effect on our results for Swedish-born and specific migrant groups, the significant 1994 pseudo-intervention date suggests that residual effects of the economic crisis may have remained.…”
Section: Original Researchmentioning
confidence: 99%
“…After ten years of continued fertility declines, countries such as Sweden, Finland and Norway experienced a fertility rebound that fueled, among others, the gender revolution theory (Goldscheider, et al, 2015). However, recent studies show that fertility has fallen again in these countries (Jalovaara, et al, 2019;Comolli, et al 2020). Due to poor evidence of an eventual fertility recovery, and the impact of the great economic recession of 2008, now aggravated by the Covid-19 crisis, material explanations have again gained strength (Seltzer, 2019;Matysiak, et al, 2020).…”
Section: Theoretical Interpretations Of Low Fertility and The Spanish Contextmentioning
confidence: 99%